Analisis Tindak Tutur Ekpresif dan Direktif dalam Film Guru-Guru Gokil Karya Sammaria Simanjuntak serta Pemanfaatannya sebagai Bahan Ajar di SMA - Winarsih, Sri (Jurnal Artikula, 2024)
Analysis of expressive and directive speech acts in the film "Guru-Guru Gokil" by Sammaria Simanjuntak and their use as teaching materials in high school. Indonesian and Regional Literature Language Education Study Program, Undergraduate Program (S1) Faculty of Teacher Training and Education, Mathla'ul Anwar University, Banten. This research aims to analyze expressive and directive speech acts in the film "Guru-Guru Gokil" by Sammaria Simanjuntak and explore their use as teaching materials at the Senior High School (SMA) level. Expressive speech acts refer to statements that reflect the speaker's feelings or emotions, while directive speech acts involve actions that influence the listener's behavior or response. The method used is a descriptive qualitative method, data collection techniques using listening techniques, data transcripts, note taking steps, analysis steps. The total data that the author has obtained is 61 data, expressive speech acts, namely 30 utterances consisting of praising 8 utterances, saying thank you 8 utterances, saying sorry 7 utterances, congratulating 2 utterances, saying hello 4 utterances, and blaming 1 utterance. 31 directive speech acts consisting of commanding 20 utterances, ordering 1 utterance, requesting 5 utterances, and giving advice 5 utterances. Apart from that, this research can be used as teaching material in class XI high school with drama text material.